Temperature Patterns over Northeast and West Coast Regions of India - Jamir, Tongdimenba; Gadgil, Alka; De, Uday; Krishnakumar, Gaddam (Bulletin of Geography. Physical Geography Series, 2016)
The study examines whether maximum/minimum temperature is responsible for warming/cooling trend. In order to accomplish this, linear regression was used in temperature series such as mean (Tmean), maximum (Tmax), minimum (Tmin) and mean monthly diurnal temperature range (DTR). A detailed analysis indicates that 11 out of 13 stations over the West Coast region (WCR) shows significant increase in mean annual temperature as a result of increase in annual Tmax. However, the Northeast region (NER) shows a mixed trend with 6/2 stations indicating significant increase/decrease in annual Tmean. Both these patterns can be ascribed to the decrease/increase in the Tmin/Tmax. 85% of the stations in DTR over the WCR shows significant increasing trend while 60% of stations in the NER show significant decreasing trend. The analysis of meteorological parameters reveals that low/medium cloud, calm days, winds, forest cover and population growth influences maximum/minimum temperature for the NER whereas low cloud cover and wind direction has an influence over the WCR.